The Cellular Origins of Chick Global Flash Multifocal Electroretinogram - Patrick W. K. Ting; Patrick H. W. Chu; Yf Ng; Henry H. L. Chan (i-Perception, 2011)
Purpose: The aim of this study was to obtain a better understanding of the cellular contributions to the chick global flash mfERG by using a pharmacological dissection method. Method: Global flash mfERGs were recorded from 11 white leghorn chicks (Gallus gallus). The inner retinal response was suppressed by injection of tetrodotoxin (TTX) and N-methyl-D-aspartic acid (NMDA). Responses from ON- and OFF-pathway were isolated by further injection of 2-amino-4-phosphonobutyric acid (APB). Results: The global flash mfERG of white leghorn chicks consist of a direct component (DC) originated from outer retina and a late induced component (IC) originated from the inner retina which are comparable to the global flash mfERG responses from primate, porcine and human. The ON- and OFF- responses found in chicks are also similar to that of porcine and primate with the N1 component is mainly from OFF-bipolar responses and the ON-response contributes mainly in the P1 component. Conclusion: Because of the similarities for the global flash mfERG found in chick to other species, this makes the possibility of using chick retina as a potential animal model for eye research in the area of mfERG.